Fragility assessment of installation defects in industrial standing seam metal roof subjected to wind loads - Kwon, Kyungrok; Choi, Hyok Chu; Ji, Koochul; Choi, Youngjin; Kong, Jung Sik (Journal of Civil Engineering and Management, 2024)
In industrial structures in which standing seam metal roofs (SSMRs) are commonly used, heat insulation and waterproofing have emerged as crucial requirements for the protection of internal equipment. However, in newly developed SSMRs, the structural systems have become increasingly complex. The installation of insulation layers between the upper and lower panels poses challenges during roof panel installations, resulting in defects owing to the carelessness of the installer. These clip defects can significantly affect the wind-resistance performance of the SSMR structure during testing. In this study, we employed finite element method (FEM) modeling and verification, utilizing the wind resistance test results of SSMRs. In addition, we conducted a variable analysis as well as a fragility assessment focusing on the location and number of clip defects in the SSMRs. The results of this study indicate that the wind performance of the roof was significantly degraded owing to SSMR clip defects. Moreover, the wind resistance performance can be quantitatively evaluated by considering the roof zone and the exposed environment under a wind load.